Strategi Penanggulangan Perkawinan Anak Pasca Putusan Mahkamah Konstitusi Nomor 22/PUU-XV/2017 Perspektif Teori Maslahah - Erfaniah Zuhriah; Imam Sukadi (Fakultas Syariah, 2022)
Abstract: This strategy to overcome child marriage in Malang Regency is important because the number of child marriages is increasing. This research was conducted in a sociological juridical manner located at the Office of Women's Empowerment and Child Protection (DP3A) Malang Regency and at the Malang Regency Religious Office. Data were collected by interview method and analyzed by content analysis. From the research conducted, it can be concluded that the Constitutional Court's Decision No. 22/PUU-XV/2017 which was followed up by Law no. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage, which raised the marriage age limit for women from 16 years to 19 years, especially in Malang Regency, has not succeeded in solving the problem and has caused its own probematics, namely the number of applications for marriage dispensation to the Malang Regency Religious Court is increasing. The strategy taken in tackling child marriage from the perspective of the masahah theory is by socializing marriage maturity through madrasas, conducting marriage guidance in each District KUA, Establishing a Counseling Information Center (PIK) as an effort to reproductive health, Providing kid genre props, Formation of human beings genre and genre ambassadors, and dissemination of reproductive health education. Another strategy is to empower the role of the family through parental supervision, as well as improve the quality of formal education for students.Keywords: child marriage; maslahah; health education. Abstrak: Strategi penanggulangan perkawinan anak di Kabupaten Malang ini penting dilakukan karena perkawinan anak semakin bertambahnya jumlahnya. Penelitian ini dilakukan secara yuridis sosiologis yang berlokasi di Kantor Dinas Pemberdayaan Perempuan dan Perlindungan Anak (DP3A) Kabupaten Malang dan di Kantor Agama Kabupaten Malang. Pengambilan data dilakukan dengan metode wawancara dan menganalisisnya dengan content Analisys. Dari penelitian yang dilakukan di dapat bahwa Putusan MK No. 22/PUU-XV/2017 yang ditindak lanjutin dengan UU No. 16 Tahun 2019 tentang Perubahan UU No. 1 Tahun 1974 tentang Perkawinan, yang menaikkan batas usia perkawinan bagi perempuan yang semula 16 tahun menjadi 19 tahun khususnya di Kabupaten Malang belum berhasil menyelesaikan masalah dan menimbulkan probematika tersendiri, yaitu jumlah permohonan dispensasi nikah ke Pengadilan Agama Kabupaten Malang semakin bertambah banyak. Strategi yang dilakukan dalam menanggulangi perkawinan anak perspektif teori masahah adalah dengan dengan melakukan sosialisasi pendewasaan perkawinan lewat madrasah, melakukan bimbingan perkawinan di masing-masing KUA Kecamatan, Pembentukan Pusat Informasi Konseling (PIK) sebagai upaya kesehatan reproduksi, Pemberian alat peraga genre kid, Pembentukan insan genre dan duta genre, dan sosialisasi penyuluhan kesehatan reproduksi. Strategi lainnya yang dilakukan adalah dengan pemberdayaan peran keluarga melalui pengawasan orang tua, serta peningkatan kualitas pendidikan formal bagi peserta didik.Kata Kunci: perkawinan anak; maslahah; pendidikan kesehatan.